Determination of Mount Merapi Volcanic Earthquake Hypocentre By Using Seismic Wave Polarization Analysis - Syahrial Ayub; Muhammad Zuhdi; Muhammad Taufik; Gunawan Gunawan (Pascasarjana, Mataram University, 2020)
Volcanic earthquakes of mount Merapi have been investigated periodically. The investigation aims to determine the hypocenter and epicenter of mount Merapi's volcanic earthquake using wave polarization analysis. The analysis was carried out in three domains, which are the time domain, the frequency domain, and the space domain. The analysis in the time domain was conducted by the arrival time of the volcanic earthquake, and the analysis in the frequency domain was done by observing the spectrum to get information on source frequency and bandwidth passed from polarization analysis, while the analysis in the space domain was conducted especially on hypocenter determination of the volcanic earthquakes. The analysis leads to the frequency of source 6 Hz and a bandwidth of 0.1 Hz. Thus, the hypocenter of volcanic earthquakes by polarization analysis was distributed to depth from 670 m to 3250 m from Merapi's top